VERBAL REPRESENTATION OF CULTURAL CONCEPTS IN COMPARATIVE LINGUOCULTUROLOGY - Ashur Abdiyevich Yakhshiyev (International Journal of Literature and Language Studies, 2026)
Abstract.This article examines the mechanisms of the verbal representation of cultural concepts in different languages from the perspective of comparative linguoculturology. The study analyzes the ways in which national cultural values, mental models, and conceptual structures are reflected in lexical, phraseological, paremiological, and onomastic units across various languages. Particular attention is paid to the interaction between language and culture as interrelated semiotic systems that shape the national worldview. Based on a comparative analysis, the study identifies both universal patterns of conceptualizing reality and nationally specific features of the linguistic representation of cultural meanings.